Collective identification and well-being in a community from the Peruvian northern coast - Espinosa, Agustín (2016)
This study examines the association between collective identification with a rural communityfrom the northern coast of Peru, and the subjective, psychological and social expressions of well-being. These variables were analyzed in a sample of 80 community residents. Resultsshow significant associations between some components of collective identification and some expressions of well-being. A path analysis suggest that the general positive self-stereotype has a positive effect on collective self-esteem, while the self-stereotype of low efficacy reduces it. Meanwhile, collective self-esteem increases the degree of identification. Self-stereotype components influence different expressions of well-being. Thus, self-stereotype of low efficacy negatively affects social well-being, and self-stereotype of corruption negatively affects psychological well-being. Finally, social well-being influences psychological well-being, which in turn influences subjective well-being.